The performance analysis of public key cryptography-based authentication - Xiong, Kaiqi (EAI Endorsed Transactions on Security and Safety, 2018)
Several Kerberos-based authentication techniques using public-key cryptography have been proposed. Public-key cryptography can be used to eliminate a single point failure problem in the Key Distribution Center (KDC) and achieve better scalability. Public Key Cryptography for Cross-Realm Authentication in Kerberos (PKCROSS) and Public Key Utilizing Tickets for Application Servers (PKTAPP, a.k.a. KX.509/KCA) are considered two notable techniques. The latter was suggested to improve the former, but their actual computational and communication times have been poorly understood. This paper first presents a thorough performance evaluation of the two protocols based on analytical analysis and queueing network models. As shown, PKTAPP does not scale better than PKCROSS. Then, this paper gives a new public key cryptography-based group authentication technique. We show that the new technique can achieve better scalability than PKCORSS and PKTAPP and our performance methodology is effective.
Keywords: Security; Performance Evaluation; Complexity Analysis